Preserving the Pampanga archives heritage a survey of resources and practices in Pampanga - Quiambao, Jonavie S. (2003)
The archives heritage serves as the wealth of every community, containing the most noteworthy forms of expression of the historical contribution made by its people to world culture. Its value stems from the esteem as the people rightly hold a component of cultural identity (UNESCO, 1988).However, interest in the past has never been greater, thus, the importance of archives is not always realized. The very realization of the importance of archives can pose a danger. Archives materials can be neglected, sometimes put up for sale, broken up, lost to the country or, still worse, sold abroad. Archives are permanent, unique, and authentic records kept for their continuing value (Coles, 1988). These include historical documents which can convey information about the past human activity, and which can supplement and clarify oral traditions.